Eosinophilic colitis in infants - Lozinsky, Adriana Chebar [UNIFESP] (2014)
Objective: to review the literature for clinical data on infants with allergic or eosinophilic colitis.Data source: MEDLINE search of all indexes was performed using the words colitis or proctocolitis and eosinophilic or colitis or proctocolitis and allergic between 1966 and February of 2013. All articles that described patients' characteristics were selected.Data synthesis: a total of 770 articles were identified, of which 32 met the inclusion criteria. the 32 articles included a total of 314 infants. According to the available information, 61.6% of infants were male and 78.6% were younger than 6 months. of the 314 patients, 49.0% were fed exclusively breast milk, 44.2% received cow's milk protein, and 6.8% received soy protein. Diarrheal stools were described in 28.3% of patients. Eosinophilia was found in 43.8% (115/263) of infants. Colonic or rectal biopsy showed infiltration by eosinophils (between 5 and 25 per high-power field) in 89.3% (236/264) of patients. Most patients showed improvement with the removal of the protein in cow's milk from their diet or the mother's diet. Allergy challenge tests with cow's milk protein were cited by 12 of the 32 articles (66 patients).Conclusions: eosinophilic colitis occurs predominantly in the first six months of life and in males. Allergy to cow's milk was considered the main cause of eosinophilic colitis. Exclusion of cow's milk from the diet of the lactating mother or from the infant's diet is generally an effective therapeutic measure. (C) 2013 Sociedade Brasileira de Pediatria. Published by Elsevier Editora Ltda. All rights reserved.